Almost Lost (The Au Pair-Book Two) - Blake, Pierce (Lukeman Literary, 2019)
"A MASTERPIECE OF THRILLER AND MYSTERY. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) ALMOST LOST is book #2 in a new psychological thriller series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has received over 1,000 five star reviews. When a divorcee vacationing in the British countryside puts out an ad for an au pair, Cassandra Vale, 23, broke, still reeling from the ruins of her last placement in France, takes the job without hesitation. Wealthy, handsome and generous, with two sweet children, she feels nothing can go wrong. But can it? Treated to the best England has to offer, and with France out of sight, Cassandra dares to believe she finally has a moment to catch her breath-until a startling revelation forces her to question the truths of her tumultuous past, her employer, and her very own sanity. A riveting mystery replete with complex characters, layers of secrets, dramatic twists and turns and heart-pounding suspense, ALMOST LOST is book #2 in a psychological suspense series that will have you turning pages late into the night. Book #3 in the series--ALMOST DEAD-is available for pre-order!
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky